ANALYSIS OF THE LOCATION EFFECT IN TWO WITHIN-DIMENSION SEARCH TASK - Ponte, Dolores; Sampedro, Mª José (Anales de Psicología / Annals of Psychology, 2007)
Analysis of the location effect in two within-dimension search task.Abstract: In this study, we explore the role played by eccentricity in two different visual search tasks (serial and parallel), along with the differences that occur in the processing of stimuli in different visual fields (upper, lower, right and left), analyzing the changes that occur with practice. The results support the attentional hypothesis of Wolfe et al, and show that the effects produced by these variables correlate to the difficulty of the task: the more attentional resources necessary, the greater the effect produced by the target location. In regard to the effects produced by practice, these are limited to provoking acceleration of responses rather than qualitative changes in the performance.